Ethyl 3-(4-hydroxyphenoxy)-2-(4-methoxyphenyl)acrylate - Jin Hou (Acta Crystallographica Section E, 2008)
In the title compound, C18H18O5, the dihedral angle between the two benzene rings is 55.2 (3)°. The ethyl acrylate linkage is planar and forms dihedral angles of 21.3 (3) and 41.0 (3)°, respectively, with the hydroxyphenyl and methoxyphenyl rings. In the crystal structure, molecules are linked into zigzag chains along the b axis by O—H...O hydrogen bonds.